Surface chlorophyll a distribution in marginal ice zone in Antarctica, 1984/85 - Fukuda, Yasushi; Ohno, Masao; Fukuchi, Mitsuo (1986)
P(論文) Chlorophyll α concentrations of surface layer were measured at 108 stations in the Antarctic waters south of 63°S including the pack ice and the fast ice regions along the course of the SHIRASE during the 1984-85 austral summer. High chlorophyll α concentration was observed in the pack ice and the fast ice regions between late December and early January. This high value seems to be correlated with the release of so-called ice algae which proliferated at the bottom part of sea ice. After the disappearance of the sea ice, chlorophyll α concentration in the open water decreased abruptly and became low. After passing through a period of two or three months, the high concentration of chlorophyll α was observed again within Lutzow-Holm Bay and Breid Bay. The growth of the planktonic algae seems to occur in these regions during the austral summer. departmental bulletin paper